Strategic analysis of the sustainable management of the cultural heritage of the Historic Center of Santa Ana de Coro, Falcón, Venezuela. : A public and tourist perspective (Ágora de Heterodoxias, 2020)
The sustainable management of cultural heritage represents a set of processes carried out by the social actors of the Historic Center of Santa Ana de Coro. In the scientific approach, the problems and the components that mediate them are described, the potentialities and power relations between the actors are characterized and the sustainable management of the cultural heritage in the Historic Center is structurally and strategically analyzed. The research is descriptive, following an empirical systemic design, in terms of the nature of the study scenario, it is described as a deficient reality due to the low level of integration between the social actors related to the management of cultural heritage. The findings reveal the provision of low quality services, the absence of a sustainable tourism marketing plan and weakness in the application of public policies directed to the Historic Center. The conclusion is that there is no management model that guarantees the sustainability of the attraction, in addition to the designation of development agents with limited managerial and technical skills for the formulation of successful public policies; the fragmented view constitutes the main strategic lines to be considered from the analysis of heritage management.
Keywords: sustainable management; public management; cultural heritage; tourism